CAN FOREIGN OWNERSHIP MODERATE THE RELATIONSHIP CORPORATE SOCIAL RESPONSIBILITY AND FINANCIAL PERFORMANCE? - Yenni Vera Fibriyanti; Ari Kuncara Widagdo (Jurnal Keuangan dan Perbankan, 2022)
COVID-19 is a global health pandemic that is currently sweeping the world and had huge impact on the world economy. Currently, all countries, including Indonesia, are paying attention to how the development of this pandemic is, as evidenced by the many media that inform the development of the pandemic and the response given by the government in overcoming it. This study was conducted with the aim of investigating how the influence provided by government information and policies related to COVID-19 on returns and stock volatility in Indonesia. Empirical findings from this study show that information on the COVID-19 pandemic (GSVI Covid), the number of positive cases, death rates, and the government tightening index during the pandemic, seem to have a negative effect on stock returns and vice versa have a positive effect on volatility. Meanwhile, with the information on the COVID-19 vaccine (GSVI Vaksin), fiscal policy in the form of growth in government spending, as well as monetary policy in the form of growth in the money supply is said to have a positive influence on stock returns, as well as reduce excessive volatility in the market.